2020
DOI: 10.1002/ppul.25005
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and pulmonary function among healthy‐weight and overweight/obese children with asthma

Abstract: Introduction Epidemiologic studies have found low/absence of atopy in obese asthmatic children, but the association or lack thereof of atopy with disease morbidity, including pulmonary function, in obese asthma is not well understood. We sought to define the association of atopy with pulmonary function in overweight/obese minority children with asthma. Methods In a retrospective chart review of 200 predominantly minority children evaluated at an academic Pediatric Asthma Center over 5 years, we compared the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…The divergence may be due to the relatively small sample size. These results were in accordance with those of other studies [ 34 , 36 ]. The similar atopic inflammatory profile might further suggest that the standard treatment with inhaled corticosteroids could be effective in obese asthmatic patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The divergence may be due to the relatively small sample size. These results were in accordance with those of other studies [ 34 , 36 ]. The similar atopic inflammatory profile might further suggest that the standard treatment with inhaled corticosteroids could be effective in obese asthmatic patients.…”
Section: Discussionsupporting
confidence: 94%
“…The baseline FEF25–75% was significantly reduced in obese patients showing a lower peripheral airflow compared to that in those with normal weight or overweight. Similarly, previous studies also showed a lower FEF25–75% in overweight or obese asthmatic children than in normal-weight children [ 31 , 34 ].…”
Section: Discussionsupporting
confidence: 66%
“…These results are further supported by a recent meta‐analysis which found the pooled RR to be 1.47 (95% CI, 1.25, 1.72) 24 . Furthermore, comorbidity was higher in boys, 20,21 black children 25 and physically inactive individuals (Figure 2). 22,26 …”
Section: Resultssupporting
confidence: 69%
“…[21][22][23] These results are further supported by a recent meta-analysis which found the pooled RR to be 1.47 (95% CI, 1.25, 1.72). 24 Furthermore, comorbidity was higher in boys, 20,21 black children 25 and physically inactive individuals (Figure 2). 22,26 The mechanisms linking asthma with obesity are unclear, but it is hypothesized that the two conditions may share common etiological pathways.…”
Section: Asthma and Obesitymentioning
confidence: 97%
“…Obesity refers to a state in which excess energy is stored as fat because energy intake is higher than energy consumption. Obesity can cause diseases such as asthma, cardiovascular disease, and diabetes ( Goran et al ., 2003 ; Farhat et al ., 2021 ). Adipose tissues (ATs) contain various immune cells, including T cells generated from the spleen or lymph node (LN), which modulate the immune response and, in turn, influence the metabolism in ATs ( Kohlgruber et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%